2005
DOI: 10.1080/10253890500147381
|View full text |Cite
|
Sign up to set email alerts
|

Stress affects dopaminergic signaling pathways inDrosophila melanogaster

Abstract: Behaviors modulated by dopamine appear to be conserved across species. In the model system Drosophila melanogaster, as in mammals, dopamine modulates female sexual receptivity, a simple form of learning and responses to drugs of abuse. Synthesis, reuptake and binding of dopamine are also evolutionarily conserved. Since stress has been shown to affect dopaminergic signaling pathways in mammals, we investigated the consequences of exposure to diverse stressors on dopaminergic physiology in the fruit fly, D. mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 45 publications
5
39
0
3
Order By: Relevance
“…We found that in F. japonica, DA levels in foraging worker brains decreased under starvation, as previously shown for 5-day-oldfemale Drosophila melanogaster (Neckameyer and Weinstein, 2005). In mice, the dopaminergic circuitry is involved in feeding, and disrupting dopamine signaling decreased motivation for eating and drinking (Narayanan et al, 2010).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We found that in F. japonica, DA levels in foraging worker brains decreased under starvation, as previously shown for 5-day-oldfemale Drosophila melanogaster (Neckameyer and Weinstein, 2005). In mice, the dopaminergic circuitry is involved in feeding, and disrupting dopamine signaling decreased motivation for eating and drinking (Narayanan et al, 2010).…”
Section: Discussionsupporting
confidence: 61%
“…Conversely, starvation stress did not affect OA levels and there was no relationship between OA and trophallaxis in the starved ants. Yet, it is well known that various stressors such as high/low temperature and high population density affect OA level in insects (Woodring et al, 1988;Rauschenbach et al, 1993;Gruntenko et al, 2004;Neckameyer and Weinstein, 2005;Chen et al, 2008). We demonstrated a slight effect of starvation on OA level and thus there may be a role for OA in starvation stress and social behavior in F. japonica.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Drosophila tyrosine hydroxylase is encoded by the pale locus (51), and mutations in the pale gene result in decreased dopamine pools in adult heads, even in the heterozygous state (22). Compared with wild type, ple mutants showed increased susceptibility toward various types of stress, including the dopaminergic toxicant paraquat, indicating that dopamine functions as a key element in the stress response (22,52). Here we also found that 1-octen-3-ol was more toxic in the ple heterozygous mutant lines.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, molecular-genetic and pharmacologic analyses have demonstrated the importance of DA in sleep, arousal, light perception, circadian entrainment, feeding, and aversive conditioning (Schwaerzel et al 2003;Andretic et al 2005;Kume et al 2005;Neckameyer and Weinstein 2005;Chang et al 2006;Draper et al 2007;Bayersdorfer et al 2010;Hirsh et al 2010;Riemensperger et al 2011); of 5-HT in aggression, place memory, circadian rhythms, and sleep (Yuan et al 2005(Yuan et al , 2006Sitaraman et al 2008;Alekseyenko et al 2010); and of OA in sleep, locomotion, female fertility, aggression, place memory, and the fly's response to environmental stressors (Hirashima et al 2000;Lee et al 2003;Fox et al 2006;Hardie et al 2007;Crocker and Sehgal 2008;Zhou et al 2008;Crocker et al 2010;Sitaraman et al 2010). However, as in mammals, the relative importance of each aminergic system for particular behaviors and their potential interplay remain unclear.…”
mentioning
confidence: 99%